2016
DOI: 10.1080/21663831.2016.1174163
|View full text |Cite
|
Sign up to set email alerts
|

Physically founded phonon dispersions of few-layer materials and the case of borophene

Abstract: By building physically sound interatomic force constants, we offer evidence of the universal presence of a quadratic phonon branch in all unstrained 2D materials, thus contradicting much of the existing literature. Through a reformulation of the interatomic force constants (IFCs) in terms of internal coordinates, we find that a delicate balance between the IFCs is responsible for this quadraticity. We use this approach to predict the thermal conductivity of Pmmn borophene, which is comparable to that of MoS 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
187
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(208 citation statements)
references
References 56 publications
19
187
0
2
Order By: Relevance
“…A 7×5×1 supercell with 7×5×1 k-mesh is used to ensure the convergence. Table I lists other typical structures for borophene as predicted in previous studies [20][21][22] . The predicted a corresponds to 1/3 the a observed in Ref.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 7×5×1 supercell with 7×5×1 k-mesh is used to ensure the convergence. Table I lists other typical structures for borophene as predicted in previous studies [20][21][22] . The predicted a corresponds to 1/3 the a observed in Ref.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…[9], while the predicted b is in good agreement with experimental results 9 . Although theoretical studies have proposed various structures for borophene [20][21][22][23][24][25][26][27][28][29][30] , scanning tunneling microscopy measurements have shown that borophene has planar structure with anisotropic corrugation 9 . There is no corrugations along the a direction, while the buckling along the b direction is observed.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…Two-dimensional (2D) boron sheet (borophene) has attracted much attention [1][2][3][4][5][6] since it was synthesized on a silver substrate under ultrahigh-vacuum 7 . While experimental progress is slow due to difficulty in synthesizing borophene under the strict experimental conditions, many first principles calculations have been performed to study the mechanical properties, electronic structure, phonon dispersion, lattice thermal conductivity, superconducting behavior and optical properties of borophene, as well as borophene nanoribbons and borophene nanotubes [8][9][10][11][12][13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…The flexural ZA mode of graphene obey a quadratic dispersion ω ZA ∝ |q| 2 , which is attributed to the sixfold rotational symmetry. [47,[55][56][57][58][59][60] The obtained phonon frequency of stanene is about ten times smaller than that of graphene because of the heavier atomic mass. The intersection of LA and ZO in graphene is absent in stanene.…”
Section: Electronic Structures and Phonon Band Dispersionsmentioning
confidence: 98%